Button accordion sonata in ukrainian music of the second hale of the twentieth century: trends in the genre evolution - Stashevskyi, Andrii (My University, 2019)
The fruitful development of academic button accordion and accordion performance in Ukraine in the second half of the twentieth century significantly contributed to the formation of their own original repertoire. Thus, during this period, a considerable number of original works for button accordion appeared, based not only on folk traditions but also on the experience of developing academic genres, including the sonata genre.
Keywords: музика акордеонна, accordion music